Mecha-Ude. Mechanical arms, 2 - Koyoka, Yoshino (Graphix, an imprint of Scholastic, 2025)
"Under the watchful eye of ARMS agent (and classmate) Aki Murasame, Hikaru and Mecha-Ude Alma are determined to unlock the mysteries of Alma's past. What secret power does he hold, making him so valuable to ARMS and target for others? And why did he lose his memories in the first place? A new "transfer student" with ties to the shadowy Kagami Group may hold the answers they're looking for... or may separate Hikaru and Alma once and for all."--